The Philosophical Meanings Of The Ma'duangan Ceremonial Culture (Patang Puloan) In Batunoni Village Anggeraja District Enrekang Regency - Alamsyah Alamsyah (Khatulistiwa, 2022)
Tradition is a word that cannot be separated from a nation, including the Indonesian nation which is a compound country with the largest multiculture in the world. Indonesia has more than 17,000 islands stretching from Sabang to Merauke, where each region has a different culture. This research aims (1) to find out the implementation of ma'duangan tradition in Enrekang regency. (2) to know the philosophical meaning and values contained in the implementation of the Ma'duangan or Patang puloan tradition. This study is ethnographic research. Data collection techniques are carried out by means of interviews and documentation, the data analysis used is qualitative descriptive analysis. The results of this study show that: (1). The implementation of the Ma'duangan or Patang Puloan tradition is the culmination of events in a series of events/rituals of death ceremonies in Batunoni Village which starts from sangbonginna (first night) which consists of two types of activities, namely day and night activities, mangbongi tallu (third night), mangbongi pitu (seventh night), and mangpatang puloan (fortieth night) consisting of two stages of the event, the first is mangpellao (lowering), the second is manggere tedong (slaughtering buffalo). (2) The philosophical meaning contained in the ma'duangan event; a. The value of togetherness and a sense of solidarity. b. Foster cooperation in the form of gotong royong. c. The value of trust is recommended to the community to maintain the noble values contained in the implementation of the Ma'duangan tradition (patang puloan) as a guideline in public life, despite the development of the times (Globalization), education and religion (belief) which is very influential on society to make changes.